No Logo: No Space, No Choice, No Jobs - Naomi Klein (Great Britain Collins Modern Classics, 2010)
NO LOGO was an international bestseller and "a movement bible" (The New York Times). Naomi Klein's second book, The Shock Doctrine, was hailed as a "master narrative of our time," and has over a million copies in print worldwide. In the last decade, NO LOGO has become an international phenomenon and a cultural manifesto for the critics of unfettered capitalism worldwide. As America faces a second economic depression, Klein's analysis of our corporate and branded world is as timely and powerful as ever. Equal parts cultural analysis, political manifesto, mall-rat memoir, and journalistic exposé, NO LOGO is the first book to put the new resistance into pop-historical and clear economic perspective. Naomi Klein tells a story of rebellion and self-determination in the face of our new branded world.
Keywords: Business; Economics; Nonfiction; Politics; Sociology; (FSD211) Advanced Fashion Product; Global Citizenship (BIN1064-N); (HRM3046-N) Current Issues in Business Ethics & CSR